Experimental Study of Water Transfer and Ice Accumulation in Freezing Soils under Different Conditions - Sihao Liang; Xinyan Ma; Qiang Li; Xinyu Ye; Jianlong Liu; Jian Zhang (Advances in Civil Engineering)
A series of tests for water transfer and ice accumulation were conducted under different soil types and conditions of water supply method, temperature gradient, and initial water content; the influence of the above parameters on the efficiency of water and vapor transfer was investigated and discussed. The main conclusions drawn are as follows. First, due to the difference in permeability for different soil type, water (i.e., liquid water and vapor) transfers differently. The water (or ice) accumulated in the soils of calcareous sand, silty soil in Lanzhou (SSL), red clay in Changsha, and silty soil in Hohhot (SSH) under the top plate is 34.5%, 21.0%, 11.33%, and 26.7%, respectively. In addition, the water (or ice) accumulation is determined by the holding capacity of water. Second, the supply method of liquid water is more efficiently compared with that of vapor supply, with the water contents increasing to 60.5% and 57.3% for liquid water and vapor supply. Third, the larger the temperature gradient, the greater the water accumulation in the frozen area. The increased amount of water mass under different temperature boundary conditions is 227.9 g, 253.3 g, and 273.8 g, respectively. Finally, the initial water content in silty soil has a significant influence on water and vapor transfer. The increased amounts of water for the tests of the initial water content of 5%, 10%, and 15% are 282.6 g, 253.3 g, and 132.5 g, respectively. The smaller the initial water content, the greater the water transfer in the unfrozen zone and vapor transfer in the frozen zone.